Globalization and regional income inequality: Evidence from within China - Guanghua Wan; Ming Lu; Zhao Chen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
China's recent accession to the WTO is expected to accelerate its integration into the world economy, which aggravates concerns over the impact of globalization on the already rising inter-region income inequality in China. This paper discusses China's globalization process and estimates an income generating function, incorporating trade and FDI variables. It then applies the newly developed Shapley value decomposition technique to quantify the contributions of globalization, along with other variables, to regional inequality. It is found that (a) globalization constitutes a positive and substantial share to regional inequality and the share rises over time; (b) capital is one of the largest and increasingly important contributor to regional inequality; (c) economic reform characterized by privatization exerts a significant impact on regional inequality; and (d) the relative contributions of education, location, urbanization and dependency ratio to regional inequality have been declining.
Keywords: C31; F02; R12; 330; globalization; inequality; decomposition; Shapley value; China; Globalisierung; Regionale Einkommensverteilung; China